Can eye-temperature variation from exercise explain behaviour profiles among trotting horses? - Berglund, Paulina (SLU/Dept. of Animal Breeding and Genetics (until 231231), 2019)
Eye-temperature measured with infrared thermography have in previous studies showed significant correlation to competition results in harness racing. Studies also show a positive correlation between serotonin level in blood and eye-temperature which indicates that this method could serve as an indicator of stress and welfare in harness racing. The purpose of this study was to measure eye-temperature during competition with the help of infrared-thermography and analyse if it could explain the behavioural profiles of the horses. A factor analysis where 5 principal components were constructed from the behaviour measures explained 71% of the variance. Horses with higher scores in factor 1 are fearful, remember unpleasant events and horses with lower scores in factor 1 tend to not desire to win and tend to not learn the task of racing. Horses with higher scores in factor 2 recovers well and are cooperative. Horses with higher scores in factor 3 are calm, horses with higher scores in factor 4 have good appetite after competitions and are focused. Horses with higher scores in factor 5 are stubborn, fearful and tend to lose control. A univariate linear model was constructed to test the significance of different co-variables. Breed had a significant effect on factor 2 and sex had a significant effect on factor 5. The eye-temperature variation could not explain the behaviours of the horses. To find strong evidence for the impact of eye-temperature on behaviour, additional interrogated horses are required to verify what exactly eye temperature is a measurement of. Future applications of these very preliminary results might lead to faster breeding progress, with better competition result and better welfare among sport horses.